Back from the dead: The world’s rarest toad Adenomus kandianus rediscovered in Sri Lanka - Wickramasinghe, L. J. Mendis; Vidanapathirana, Dulan Ranga; Wickramasinghe, Nethu (Zootaxa, 2012)
Adenomus kandianus Günther (1872) was previously known only from two specimens both deposited in the British Museum,the holotype BMNH1947.2.20.63, and the syntype of A. kelaarti BMNH1947.2.20.62. The only record of A. kandianus sincethe initial description in 1872 was by Ferguson in 1876, who mentions two specimens resembling Bufo kandianus in hiscollection, making A. kandianus the world’s rarest toad. The species had not been reported since, and was considered extinct. Here we report on its rediscovery.